STRATEGI DAN INOVASI PENDIDIKAN MADRASAH - Anwar, Chairul; Anwar, Syaiful; Wasehudin, Wasehudin; Andriansah, Zjulpi; Ananda, Rizki; Kasturi, Rima (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
ABSTRACT Madrasahs, as formal Islamic educational institutions, play a strategic role in shaping religiously grounded generations capable of competing in the global era. However, in practice, madrasahs still face serious challenges such as managerial limitations, lack of pedagogical innovation, and disparities in access to educational technology. This study aims to explore educational strategies and innovations in madrasahs that are relevant and adaptive to contemporary needs. The research employed a library research method using a descriptive qualitative approach, analyzing books, scientific journal articles, and policy documents published between 2015 and 2024. Data analysis was conducted through content analysis, focusing on three main aspects: managerial strategy, pedagogical innovation, and the integration of digital technology. The findings reveal that the success of madrasah transformation depends on visionary leadership, the strengthening of an innovation-oriented culture, and active community support. Innovative learning approaches that integrate Islamic values with modern pedagogy have been proven to improve both the quality of learning processes and outcomes. The digitalization of madrasah education presents strategic opportunities that must be supported by adequate infrastructure and competent human resources. This study concludes that a paradigm shift is essential—from conventional administrative management toward transformative and innovative educational leadership. The study offers a conceptual reference for future policy development and practical applications in the advancement of madrasah education. ABSTRAK Madrasah sebagai lembaga pendidikan Islam formal memiliki peran strategis dalam membentuk generasi religius yang sekaligus mampu bersaing di era global. Namun, dalam praktiknya, madrasah masih menghadapi tantangan serius seperti keterbatasan manajerial, rendahnya inovasi pembelajaran, serta ketimpangan dalam akses teknologi pendidikan. Penelitian ini bertujuan untuk mengkaji strategi dan inovasi pendidikan madrasah yang relevan dan adaptif terhadap kebutuhan zaman. Metode yang digunakan adalah studi literatur (library research) dengan pendekatan kualitatif deskriptif, melalui analisis terhadap buku, artikel ilmiah, dan dokumen kebijakan yang diterbitkan dalam kurun waktu 2015–2024. Analisis dilakukan melalui pendekatan content analysis dengan fokus pada tiga aspek utama: strategi manajerial, inovasi pedagogis, dan integrasi teknologi. Hasil penelitian menunjukkan bahwa keberhasilan transformasi pendidikan madrasah bergantung pada kepemimpinan yang visioner, penguatan budaya inovasi, dan dukungan komunitas yang aktif. Inovasi pembelajaran yang mengintegrasikan nilai-nilai Islam dengan pendekatan pedagogis modern terbukti meningkatkan kualitas proses dan hasil belajar. Digitalisasi pendidikan madrasah menjadi peluang strategis yang harus diimbangi dengan kesiapan infrastruktur dan kompetensi sumber daya manusia. Simpulan dari penelitian ini menegaskan pentingnya pergeseran paradigma dalam pengelolaan madrasah dari yang bersifat administratif-konvensional menjadi transformatif-inovatif. Penelitian ini diharapkan dapat menjadi rujukan konseptual bagi pengembangan kebijakan dan praktik pendidikan madrasah di masa depan.